Enhancing the economic collaboration between university and industries - Ahmad Zaharudin Idrus, Tan Sri, Datuk, Dr., 1944-; International Conference on Selangor State Investment Opportunies 1998 (INSEL '98) & Exposition on Selangor State Development 1998 (EXSEL '98) (1998 : Kuala Lumpur)
44